Uji Aktivitas Antioksidan Formulasi Krim Kombinasi dari Ekstrak Etanol Kulit Terong Ungu dan Kubis Ungu dengan Metode DPPH: Uji Aktivitas Antioksidan Formulasi Krim Kombinasi dari Ekstrak Etanol Kulit Terong Ungu dan Kubis Ungu dengan Metode DPPH - Sanjiwani, Ni Made Sukma Sanjiwani; I Wayan, Sudiarsa; Ni Putu Ayu, Mirah Mariati; Ni Kadek, Refi Mariska; Ketut, Adelia Vinanda (Program Studi Pendidikan Matematika dan Pendidikan Biologi Universitas PGRI Mahadewa Indonesia, 2023)
ABSTRACT Use cream made from active herbs as antioxidants the more increase. one among them is cream combination from extract ethanol skin eggplant purple and cabbage purple. Vegetables which have antioxidants superior that is eggplant purple and cabbage purple. Content chemical nasunin on eggplant purple have activity significant for radicals free to have role mainly on the situation like inflammation, aging, cancer and disease cardiovascular. Nasunin is the anthocyanins centralized there is on skin eggplant purple. Cabbage purple is varieties the cabbage have antioxidants highest than other cabbage. Study this aim for knowing activity antioxidants from three cream formulas combination from extract ethanol skin eggplant purple and cabbage purple. Extraction skin eggplant purple and cabbage purple conducted with method maceration for 3x24 hours and concentrated with evaporator as well evaporated. Results obtained is extract thick skin eggplant purple and cabbage colored purple chocolate old. On research this blended cream preparation from ethanol extract of purple eggplant skin and purple cabbage with three formulations, with the addition of purple eggplant skin ethanol extract and cabbage purple on each Formulas 1, 2 and 3 that is 1 and 5, 3 and 7,5 and 5 and 2.5%. The results obtained on manufacture cream is formula 2 cream has color the darkest brown than cream formula 1 and 3. Cream the analyzed activity the antioxidants with method DPPH. Cream combination from extract ethanol skin eggplant purple and cabbage purple formulas 1, 2 and 3 each have an IC of 50 consecutive 295.5 ppm, 193 ppm and 246.9 ppm. Formula 2 has the smallest IC 50 value than Formula 1 and 3 p this means formula 2 has activity more antioxidants good than formulas 1 and 3, so formula 2 comparison concentration the extract more good than Formulas 1 and 3. Keywords : cream, skin eggplant purple, cabbage purple, IC50 and DPPH